Is ‘GOLD’ standard for the management of COPD in clinical practice? - Barbara Yawn (Drugs in Context, 2012)
Summary: primary therapy for chronic obstructive pulmonary disease (COPD) is the removal of the toxic agent (in most cases, tobacco smoke). Additional therapy includes bronchodilators. Inhaled corticosteroids and long-acting bronchodilators can be used to prevent and reduce the risk of exacerbations. COPD is a systemic disease and often requires therapy of its protean-associated morbidities from depression to osteoporosis and muscle wasting. Despite pessimism from some, COPD is treatable.